The phenomenon of omission in Maqamat Al-Hariri (d. 516 AH): A Textual and Grammatical study - Mohe Al-Deen, Basil Mohammed (Al-Adab Journal, 2022)
The omission is one of the units of brevity in the Arabic language. The Arab has used, omission in the singular, and plural forms and in the letters and the Diacritics (short vowel forms), and it does not occur except with evidence indicating it, and the early Arabic scholars have been aware of that, its ultimate goal is to request an abbreviation that does not violate the meaning, if the deleted (letters, words, sentences) occur, the speech would lose its status ,eloquence and goodness Deletion is a textual phenomenon that has an effective impact on the consistency of the text and the coherence of its elements.The objective of this research is to monitor the phenomenon of omission in a linguistic blog, Maqamat Al-Hariri (d. 526 AH), which includes texts from language anecdotes, and anecdotes of structures, and phrases in a rhyming style and a rich glossary of vocabulary.Besides, shedding light on the omission and concealing (axis of the study) due to their importance in the textual and syntactic studies because omission is not only brevity and mitigation Due to frequent rotation of the words in their speech, nevertheless, the purpose of it is to amplify and glorify because of the delusion that it contains. The research adopted a presentation of selected texts from the Maqamat Al-Hariri, especially the omitted ones in which there are multiple omissions between a noun, a verb, a letter, sentences and structures with incomplete meaning and their grammatical analysis as well as highlighting the textual dimensions of these selected texts.